2015
DOI: 10.1007/s11886-015-0593-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Functional Foods on Prevention of Cardiovascular Disease and Diabetes

Abstract: A healthy dietary pattern is a cornerstone for the prevention and treatment of cardiovascular disease (CVD) and type 2 diabetes (T2DM). Compelling scientific evidence has shown many health effects of individual foods (including herbs and spices), beverages, and their constituent nutrients and bioactive components on risk of chronic disease and associated risk factors. The focus of functional foods research that is reviewed herein has been on assessing the health effects and underlying mechanisms of action of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 113 publications
0
54
0
2
Order By: Relevance
“…Although the interest of consumers in the health benefits of food has grown, flavor and texture are the two main driving forces for consumer acceptance of a product (Sikand, Kris‐Etherton, & Boulous, ). The use of peanut skins to enhance the functional properties of the coated peanuts must not destroy the flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Although the interest of consumers in the health benefits of food has grown, flavor and texture are the two main driving forces for consumer acceptance of a product (Sikand, Kris‐Etherton, & Boulous, ). The use of peanut skins to enhance the functional properties of the coated peanuts must not destroy the flavor.…”
Section: Resultsmentioning
confidence: 99%
“…We estimated the quality or relative healthfulness of the ingredients used to prepare beans or rice by allocating 2 points for ‘always’ adding herbs, spices, or vegetables rated as healthful [28], 1 point for ‘sometimes’ adding the ingredient, and 0 points for not adding the ingredient, and then summing the points. Use of English sauce and bouillon cubes, which are high in sodium and thus considered unhealthy [29],were reverse-coded.…”
Section: Methodsmentioning
confidence: 99%
“…A healthy heart and circulation system could benefit from a balanced diet with adequate fruits and vegetables. Epidemiological evidence supports a significantly positive correlation between eating fruits and vegetables and cardiovascular health [23,24,25,26]. Several studies reported healthy dietary patterns containing adequate fruits and vegetables show good results with respect to blood pressure control [27,28,29], and some studies found that there was a positive association between consuming fruits and vegetables and blood lipids control [30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%